1987
DOI: 10.2118/14898-pa
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Miscible Displacements in Laboratory Cores

Abstract: Summary. Results of stable, first-contact miscible displacements are presented for three San Andres carbonate cores from west Texas and eastern New Mexico. All three cores showed evidence of significant heterogeneity at the core scale. Effluent composition measurements were interpreted with two relatively simple models of mixing during flow in heterogeneous porous media: the Coats-Smith (CS) model, which represents the pore space as flowing and stagnant fractions with mass transfer between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
3

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 17 publications
2
14
0
3
Order By: Relevance
“…Those results revealed that the stagnant portion of the fluid was relatively constant as flow rate was increased, whereas the velocity profile in the individual (mobile) pores increased and flattened, consistent with an increased value of . Figure 7b indicates that the mass transfer coefficients obtained in this study were comparatively consistent with the ones described in literature (Baker, 1977;Batycky et al, 1982;Bretz and Orr Jr., 1987;Orr Jr. and Taber, 1984;Spence Jr. and Watkins, 1980). The resultant corrected dispersion coefficients (K corr ) and their corresponding experimental conditions (T, p and u m ) for the Estaillades and Ketton carbonates, as well as new high velocity data obtained for the Donnybrook sandstone, are listed in Table 2.…”
Section: Difference In Sandstone and Carbonate Pulse Breakthrough Curvessupporting
confidence: 89%
See 2 more Smart Citations
“…Those results revealed that the stagnant portion of the fluid was relatively constant as flow rate was increased, whereas the velocity profile in the individual (mobile) pores increased and flattened, consistent with an increased value of . Figure 7b indicates that the mass transfer coefficients obtained in this study were comparatively consistent with the ones described in literature (Baker, 1977;Batycky et al, 1982;Bretz and Orr Jr., 1987;Orr Jr. and Taber, 1984;Spence Jr. and Watkins, 1980). The resultant corrected dispersion coefficients (K corr ) and their corresponding experimental conditions (T, p and u m ) for the Estaillades and Ketton carbonates, as well as new high velocity data obtained for the Donnybrook sandstone, are listed in Table 2.…”
Section: Difference In Sandstone and Carbonate Pulse Breakthrough Curvessupporting
confidence: 89%
“…This model has been used for several dispersion studies on carbonate rocks (Baker, 1977;Batycky et al, 1982;Bretz and Orr Jr., 1987;Bretz et al, 1988;Brigham, 1974;Spence Jr. and Watkins, 1980). Equation (4) and (5) may be analytically solved for a pulse input where semi-infinite initial-boundary conditions were assumed (Goltz and Roberts, 1986;van Swaaij, 1967;Villermaux and Van Swaaij, 1969):…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To capture these effects, some authors have used dispersivity coefficients that increase with the distance travelled (Barry & Sposito 1989;Walsh & Withjack 1994), while others have invoked new physical mechanisms, such as the mass transfer between the flowing fluid and a given fraction of the pore volume that is assumed to be immobile (Coats & Smith 1964). The latter is often referred to as the 'capacitance model' and has found widespread use particularly in the petroleum literature (Donaldson et al 1976;Baker 1977;Bretz & Orr Jr 1987;Grattoni et al 1987;Honari et al 2015). The fact that structures where fluid stagnates are not readily found in many sandstones has led to the acknowledgment that anomalous transport in rock samples may instead originate from macroscopic heterogeneities, i.e.…”
Section: Laboratory Observations Of Miscible Displacements In Reservomentioning
confidence: 99%
“…Experimental studies of transport behavior in carbonate rock in both the laboratory [ Baker , ; Bretz and Orr , ; Gist et al ., ; Hidajat et al ., ; Oshita and Okabe , ; Fourar et al ., ; Fourar and Radilla , ] and the field [ Cacas et al ., ; Gelhar et al ., , and references therein; Maloszewski and Zuber , ; Meigs and Beauheim , ; Witthüser et al ., ; Birk et al ., ; Gouze et al ., ] have typically found an early breakthrough of the solute and a long tailing of the concentration at late times. At the core scale, effluent breakthrough curves (BTCs) of a sucrose tracer injected into brine‐saturated San Andres carbonate cores have shown a considerable degree of tailing due to significant core heterogeneity [ Bretz and Orr , ]. Gist et al .…”
Section: Introductionmentioning
confidence: 99%